Double doping of conjugated polymers with monomer molecular dopants - Kiefer, David; Kroon, Renee; Hofmann, Anna I.; Sun, Hengda; Liu, Xianjie; Giovannitti, Alexander; Stegerer, Dominik; Cano, Alexander; Hynynen, Jonna; Yu, Liyang; Zhang, Yadong; Nai, Dingqi; et al. (Nature materials, 2019)
A monomer molecular dopant with high electron affinity is shown to accept up to two electrons from conjugated polymers with low ionization efficiency and then generate free charge carriers with an efficiency of up to 170%.